2015
DOI: 10.1108/jcp-01-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Homicide-suicide offences: description, classification and short case studies

Abstract: Purpose – Although homicide-suicide (H-S) offences are rare, they have remarkably tragic consequences. The purposes of this paper are to: examine the background characteristics of H-S offenders (including previous offending history and psychiatric elements); describe the crime-scene behavior and examine the motivational aspects of the offences; and to establish the reliability in the outlined typologies. Design/methodology/approach – The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the other hand, this study, among many others, has shown that most homicide‐suicide offenses take place within intimate partner relationships, especially in the case of divorce . The offenses are often a quick reaction to the fact that the offender cannot sustain the relationship , and although these offenders may experience this as a mental trauma, in such a short time interval most will likely not have developed depression (at least not in the sense of a conventional clinical diagnosis). Rather, the mental status is in line with what in psychiatric terms is called a maladaptive stress reaction, in this case a reaction to the interpersonal crisis (cf.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, this study, among many others, has shown that most homicide‐suicide offenses take place within intimate partner relationships, especially in the case of divorce . The offenses are often a quick reaction to the fact that the offender cannot sustain the relationship , and although these offenders may experience this as a mental trauma, in such a short time interval most will likely not have developed depression (at least not in the sense of a conventional clinical diagnosis). Rather, the mental status is in line with what in psychiatric terms is called a maladaptive stress reaction, in this case a reaction to the interpersonal crisis (cf.…”
Section: Discussionmentioning
confidence: 76%
“…They estimate 1650 deaths annually as a result of homicide‐suicide in the United States. Previous Swedish studies have reported that the rate is 0.55 per 100,000 inhabitants in the 1970s and 0.05 per 100,000 inhabitants in the years 2007–2009 . According to Coid , homicide‐suicide rates should be similar in different countries regardless of the homicide rate.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Cross-sectional and prospective studies elucidate an association between suicidal behavior (attempted and completed suicides) and higher levels of lifetime aggression (Jokinen et al, 2010). As demonstrated in previous research (Liem, 2010;Manning, 2015;Sturup & Caman, 2015) and study II, homicide followed by the perpetrators' suicide is mainly associated with IPH, in which involuntary loss of intimacy seems to play a central role. Numerous studies have supported the notion that H-S almost exclusively involves male perpetrators with female victims (Belfrage & Rying, 2004;Bossarte et al, 2006;Campbell et al, 2007).…”
Section: Intimate Partner Homicide-suicidementioning
confidence: 69%
“…The Forensic Homicide Database includes sufficient number of cases in order to enable detection of generalizable patterns and subtypes, but manageable enough in order to enable comprehensive and detailed information in which the complex nature of the homicide event can be scrutinized. The material that the database is built on allows micro level examination, in which the cases can be examined beyond general patterns and study the dynamics and complexities involved, as is done in a case study of H-S offenses (see Sturup & Caman, 2015) that is outside the scope of the present thesis, and to some extent in study IV.…”
Section: Overall Methods and Level Of Investigationmentioning
confidence: 99%
“…In Sweden, a declining incidence of homicide-suicides has been reported for the period 1991-2010 (Regoeczi, Granath, Issa, Gilson, & Sturup, 2016). Since homicide-suicide offenders cannot be interrogated post offense, the circumstances that precede such tragic events are sometimes difficult to disentangle, and police investigators and researchers may have to rely on notes left behind by the perpetrator as the only source of information (Sturup & Caman, 2015;Weeke & Oberwittler, 2017). It has been debated whether homicide-suicides have more in common with suicides -and therefore should be thought of as "extended suicides"or whether the homicidal event is the primary motivation underlying these violent acts (Manning, 2014;Marzuk, Tardiff, & Hirsch, 1992).…”
Section: Homicide-suicidementioning
confidence: 99%